Enhancing pancreatic cancer treatment: the role of H101 oncolytic virus in irreversible electroporation - Xi, Pu; Zeng, Dejun; Chen, Miao; Jiang, Lingmin; Zhang, Yu; Qin, Dailei; Yao, Zehui; He, Chaobin (Frontiers in Immunology, 2025)
BackgroundIrreversible Electroporation (IRE) offers a promising treatment for pancreatic cancer by using high-voltage pulses to kill tumor cells. But variations in tumor size and shape can lead to uneven electric fields, causing some cells to undergo only reversible electroporation (RE) and survive. However, RE can temporarily increase the permeability of the cell membrane, allowing small molecules to enter. H101 virus is an oncolytic adenovirus with deleted E1B-55kD and E3 regions that selectively targets and kills tumor cells. This study aimed to investigate whether the H101 oncolytic virus can serve as a supplementary therapeutic approach to kill tumors combined with RE.MethodsWe first explored how RE and the H101 oncolytic virus, both individually and together, affected tumor cell proliferation and migration in cellular experiments. Subsequent in vitro studies further assessed the effects of different treatments on tumor growth. To understand the mechanisms of pathway changes in tumors from different treatment groups, we analyzed tumor samples from each group using bulk RNA sequencing (bulk RNA-seq) and single-cell RNA sequencing (scRNA-seq). Additional biochemical techniques were used to validate key molecular changes.ResultsThe combination of RE with the H101 oncolytic virus effectively inhibited pancreatic cancer cell proliferation and migration. Experiments using mouse subcutaneous tumor models confirmed that the combination therapy significantly reduced tumor growth. Further analysis bulk RNA-seq and scRNA-seq revealed that this combined approach activates the JNK-MAPK pathway, inducing apoptosis and enhancing therapeutic effects.ConclusionsThis combination boosts therapeutic effectiveness by activating the JNK-MAPK pathway and promoting tumor cell apoptosis. These findings suggest that the H101 oncolytic virus could serve as a valuable adjunct to improve the efficacy of IRE treatment.